2016
DOI: 10.1103/physreve.93.042215
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic and ballistic dynamics in time-driven quasiperiodic lattices

Abstract: We investigate the nonequilibrium dynamics of classical particles in a driven quasiperiodic lattice based on the Fibonacci sequence. An intricate transient dynamics of extraordinarily long ballistic flights at distinct velocities is found. We argue how these transients are caused and can be understood by a hierarchy of block decompositions of the quasiperiodic lattice. A comparison to the cases of periodic and fully randomized lattices is performed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In this regard, it is worth noticing that a decomposition scheme based on the mirror reversed AB and AAB atomic clusters has been recently considered, in order to study the dynamics of classical particles in a time-driven Fibonacci lattice. [45] Alternatively, one may consider non-minimal blocking schemes allowing for an exact decomposition of the M N matrix string in terms of longer atomic clusters, in such a way that the resuting bloking schemes also preserve the characteristic aperiodic order of the structure. For instance, by introducing the block matricesR…”
Section: Local Transfer Matrices Classi…cationmentioning
confidence: 99%
“…In this regard, it is worth noticing that a decomposition scheme based on the mirror reversed AB and AAB atomic clusters has been recently considered, in order to study the dynamics of classical particles in a time-driven Fibonacci lattice. [45] Alternatively, one may consider non-minimal blocking schemes allowing for an exact decomposition of the M N matrix string in terms of longer atomic clusters, in such a way that the resuting bloking schemes also preserve the characteristic aperiodic order of the structure. For instance, by introducing the block matricesR…”
Section: Local Transfer Matrices Classi…cationmentioning
confidence: 99%
“…four sequences are also examples of automatic sequences, which are sequences that can be generated by certain kinds of finite automata. The first three (FW, TM and RS) are known to have applications to condensed matter physics [15][16][17] The remaining two sequences are a random sequence with equal probabilities for +1 and -1, i.e., a fair coin tossing, and the periodic sequence (− + − + − + ...). Ignoring the cases where N is odd, for which its definition is ambiguous, the complexity of the periodic case is simply B = ln 2.…”
Section: Complexity Valuesmentioning
confidence: 99%
“…A rigorous mathematical framework for the description of symmetry breaking leading to local symmetries has been developed in [21][22][23], where nonlocal invariant currents have been identified as remnants of broken global symmetries. In [24] it was shown that the long-range order and complexity of lattice potentials generated by well-known binary aperiodic one-dimensional sequences can be encapsulated within their local symmetry structure, while in [25] the case of driven lattices was discussed. The scattering properties of quantum and photonic aperiodic structures were discussed in [26,27], answering the puzzling question about the existence of perfect transmission resonances in aperiodic systems and also providing a classification scheme with respect to their kind.…”
Section: Introductionmentioning
confidence: 99%